Statyka i Dynamika Mało Wyniosłych Powłok Ortotropowych o Stałych Krzywiznach - Królak, M. (Engineering Transactions, 1972)
The paper deals with the problems of static bending and free vibrations of orthotropic shells with constant curvatures and a constant twist of the middle surface of the shell. Shallow shells with a rectangular projection are considered; arbitrary load is normal to the middle surface. The solution of the system of partial differential equations is obtained by means of the Fourier series and the displacement potentials. The paper is illustrated by several numerical examples.